Fungal Chitin Reduces Platelet Activation Mediated via TLR8 Stimulation - Leroy, Jordan; Bortolus, Clovis; Lecointe, Karine; Parny, Melissa; Charlet, Rogatien; Sendid, Boualem; Jawhara, Samir (Frontiers in Cellular and Infection Microbiology, 2019)
Platelets play an important role in the innate immune response. During candidaemia, circulating fungal polysaccharides, including chitin, are released into the bloodstream and can interact with platelets and induce modulation of platelet activities. However, the role of circulating chitin in platelet modulation has not been investigated. The aims of the present study were to assess the effect of fungal chitin on activation, adhesion, aggregation and receptor expression of platelets and their impact on the host defense against Candida albicans. Platelets pre-treated with different concentrations of chitin (10–400 μg/mL) extracted from C. albicans were analyzed in terms of activation, Toll-like receptor (TLR) expression, aggregation and adhesion to C. albicans. Chitin treatment reduced platelet adhesion to C. albicans and neutrophils. P-selectin expression was significantly decreased in platelets challenged with chitin. Aggregation and intracellular Ca2+ influx were also decreased in platelets. TLR8 mRNA and proteins were expressed in platelets pre-treated with chitin when compared to untreated platelets. Overall, chitin purified from C. albicans reduced the adhesion, activation and aggregation of platelets mediated via TLR8 stimulation by decreasing intracellular Ca2+ influx and P-selectin expression.